New frontiers in agricultural geography: transformations, food security, land grabs and climate change - Guy M. Robinson (Boletín de la Asociación de Geógrafos Españoles, 2018)
Agriculture as a central focus of study featured prominently at several different times in the historical development of human geography, but it has also been an important contributor to the disciplinary transformation that has occurred since 1970. This essay outlines this more recent history, arguing that agricultural geography developed its own concepts and concerns, paralleling some of those within the wider discipline. It illustrates how in the past two decades attempts to examine changes occurring across the breadth of the agri-food system (from supply, to production, to consumption) have brought about a more issues-focused agricultural geography. There is discussion of the use of broad overarching concepts, which have conceived of changes to agriculture and the agri-food system in terms of episodic developments. This has seen recognition of different food regimes, acknowledging possible transitions from productivism to post-productivism to multifunctionality and perhaps neo-productivism. Having discussed these concepts, drawing extensively upon literature written in English, the essay then focuses on selected major problems or key issues to which agriciultural geographers are currently contributing new insights, namely the closely related topics of food security, land grabs and adaptations to climate change.